Model View Controller Method For Animal Care (Petcare) Information System At Niz Petcare Lawang - Iqbal Ramadhani Mukhlis; Deny Hermansyah; Tika Ayu Hariyanti (JEECS (Journal of Electrical Engineering and Computer Sciences), 2023)
Pet Care is a company that offers animal care services that are equipped with a variety of pet shop products such as food, vitamins and care. In addition to Daily Pet Care selling pet supplies and also offering animal medical and treatment services. on one computer. Pet sitting services are one of the best solutions for the majority of Indonesian people who have pets but have to travel far and cannot bring their pets with them. The owners of Niz Petcare see this as a great business opportunity. However, currently they still use manual recording in their business processes, sometimes resulting in loss of material and customer confidence. The purpose of this research is to solve this problem by designing a flow and design of a petcare application prototype that is integrated and more organized using information technology that is developing rapidly and makes it easier for customers to access online. Given these needs, the authors apply the prototyping method to accommodate these needs. The implementation of making software uses the model view controller (MVC) method which adopts the CodeIgniter framework. In this study, an evaluation was carried out using UAT and Usability Testing with ISO/IEC 9126. The evaluation results show that the application of the MVC method can produce good software products that work according to their functionality. Based on the ISO/IEC 9126 percentage, the criteria with the greatest value for understanding on P05, P07, and P09 is 89%, usability on P05 is 89%, and learning on P07 is 89% and 88% power handling at P10. From the results of the summary of the evaluation, it can be concluded that there are if the users of the system are owners, customers, administrators, fully aware of the ease of understanding, learning, use and attractiveness of the NIZ pet care information system created